Let's carefully solve the equation step by step, including distribution, combining like terms, and applying relevant properties.
Given equation:
\[ 2(x - 3) + 21 = -3 \]
Step 1: Distribute
Distributing the \(2\) to both terms inside the parentheses: \[ 2(x) - 2(3) + 21 = -3 \] This gives: \[ 2x - 6 + 21 = -3 \]
Step 2: Combine like terms
Now combine \( -6 \) and \( 21 \): \[ 2x + 15 = -3 \]
Step 3: Use the Subtraction Property of Equality
To isolate the term with \( x \), subtract \( 15 \) from both sides: \[ 2x + 15 - 15 = -3 - 15 \] This simplifies to: \[ 2x = -18 \]
Step 4: Use the Division Property of Equality
Next, divide both sides by \( 2 \): \[ \frac{2x}{2} = \frac{-18}{2} \] This simplifies to: \[ x = -9 \]
Final Answer:
\[ x = -9 \]
Thus, the final solution we have found is \( x = -9 \).
Summary of Responses:
- Distribute to get: 2x - 6 + 21 = -3
- Combine like terms to get: 2x + 15 = -3
- Use the Subtraction Property of Equality to get: 2x = -18
- Use the Division Property of Equality to get: x = -9